A Novel Nutraceuticals Mixture Improves Liver Steatosis by Preventing Oxidative Stress and Mitochondrial Dysfunction in a NAFLD Model - Sangineto, Moris (Nutrients, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the leading cause of liver disease globally, and represents a health care burden as treatment options are very scarce. The reason behind the NAFLD progression to non-alcoholic steatohepatitis (NASH) is not completely understood. Recently, the deficiency of micronutrients (e.g., vitamins, minerals, and other elements) has been suggested as crucial in NAFLD progression, such that recent studies reported the potential hepatic antioxidant properties of micronutrients supplementation. However, very little is known. Here we have explored the potential beneficial effects of dietary supplementation with FLINAX, a novel mixture of nutraceuticals (i.e., vitamin E, vitamin D3, olive dry-extract, cinnamon dry-extract and fish oil) in a NAFLD model characterized by oxidative stress and mitochondrial function impairment. Steatosis was firstly induced in Wistar rats by feeding with a high-fat/high-cholesterol diet for 4 weeks, and following this the rats were divided into two groups. One group (n = 8) was treated for 2 weeks with a normal chow-diet, while a second group (n = 8) was fed with a chow-diet supplemented with 2% FLINAX. Along with the entire experiment (6 weeks), a third group of rats was fed with a chow-diet only as control. Statistical analysis was performed with Student’s T test or one-way ANOVA followed by post-hoc Bonferroni test when appropriate. Steatosis, oxidative stress and mitochondrial respiratory chain (RC) complexes activity were analyzed in liver tissues. The dietary supplementation with FLINAX significantly improved hepatic steatosis and lipid accumulation compared to untreated rats. The mRNA and protein levels analysis showed that CPT1A and CPT2 were up-regulated by FLINAX, suggesting the enhancement of fatty acids oxidation (FAO). Important lipoperoxidation markers (i.e., HNE- and MDA-protein adducts) and the quantity of total mitochondrial oxidized proteins were significantly lower in FLINAX-treated rats. Intriguingly, FLINAX restored the mitochondrial function, stimulating the activity of mitochondrial RC complexes (i.e., I, II, III and ATP-synthase) and counteracting the peroxide production from pyruvate/malate (complex I) and succinate (complex II). Therefore, the supplementation with FLINAX reprogrammed the cellular energy homeostasis by restoring the efficiency of mitochondrial function, with a consequent improvement in steatosis.